Navigating the Ethical Terrain of AI in Rural Tourism: Privacy and Data Security Imperatives - Kumar, Pawan; Mahajan, Samriti (Journal of Neonatal Surgery, 2025)
As artificial intelligence (AI) becomes more integrated into rural tourism, ethical issues, particularly regarding privacy and data security, are increasingly important. This study delves into these concerns to foster trust and encourage responsible AI implementation. It examines existing privacy laws within rural tourism, evaluating their adequacy in addressing the unique characteristics of these areas. The paper further investigates how AI heightens challenges related to the collection, storage, and use of personal data. With a focus on AI-driven data security, it explores the potential vulnerabilities to breaches and cyberattacks that rural tourism systems face. The analysis considers the risks associated with growing digital interconnectedness, affecting both visitors and local populations. By exploring these ethical concerns, the paper highlights the potential threats AI poses to rural destinations. It calls for collaborative efforts among stakeholders to establish robust privacy safeguards, promote ethical AI practices, and ensure the protection of individual rights in rural tourism settings